The necessity of the Black Sea region transport structure improvement - L.V. Nazarova (Економіка, управління та адміністрування)
The transport structure of a region is a necessary condition for its development, so, its significance increases along with the reinforcement of globalization and integration processes. The study is relevant because the growth of the numerous cargo companies highlights the necessity of transport and logistics systems creation, which are able to function as a transport complex. This complex should not only perceive and use new market technologies in its activity, but also generate them, taking into consideration their internal needs in real time. The purpose of the research paper is to rationalize the necessity of the complex development of a region, considering the optimal choice of strategic priorities for regional transport and logistics systems aimed at optimization of material flows. The paper also contributes to the development of a logistics strategy of a region along with the creation of a balance set of policies and a developed logistics infrastructure of a region that would allow to ensure the higher level of regional logistics system development. The author has developed the algorithm of the logistic system product distribution (LSPD) that functions in two directions. The first one functions along with the creation of the system, when goals and necessary resources are being studied, so, the development and selection of the LSPD functioning options take place. The second direction occurs when the LSPD has been already developed, so, its main purpose becomes the permanent monitoring of its state and providing necessary adjustments. The complex of qualitative and quantitative parameters, that reflect the efficiency of supply chains are also developed by the author. They allow to diagnose the development of the logistic system product distribution. The author concludes that analyzing the dynamics and the structure of material flows, such factors as the character of regional specifics, the features of logistic and consumer goods, the degree of the region involvement in the interregional exchange and foreign economic activity, and the level of transport and communication system development should be taken into consideration. The main reasons for cargo limitations of the Black Sea region have been revealed. The beneficial geographical location of the Black Sea node, that caused its significant role in overall Ukrainian transport system, is highlighted. As a result of the research, the author concludes that along with the creation of the regional model of transport and logistics complexes such principles as synergy, integrity, complexity, innovation development and diversification should be taken into account. They would provide clear coherence of the regional economy stakeholders in order to achieve the common goal that is to implement the strategic plan of regional development and to increase standard of living of the region.